Physical and Chemical Properties of Benggang Soils and Their Interior Differentiation - Zhuo Ruina; Liu Xilin; Yue Meng (Shuitu baochi tongbao)
[Objective] The physical properties and their internal differentiations, and the mineral compositions and chemical elements of Benggang soil were studied in order to provide a theoretical reference for a better understanding on the benggang erosion processes. [Methods] Taking three typical Benggangs in Deqing County, Guangdong Province as examples, the methods of screening, drying, laser particle size analysis, liquid plastic limit analysis, X-ray diffraction analysis, and X-ray fluorescence spectrometry were used, to measure the basic physical properties, mineral composition and chemical elements in the different landform positions of the Benggang soil. [Results] ① Soil bulk densities of the headwalls were slightly larger than those of the colluvium, gully and diluvial fan. The water contents and limit water content of headwalls and colluvium were greater than those of the gully and diluvial fan. ② The median particle sizes of the soils were headwall < colluvium < gully sediments < diluvium. Grain size distributions of the headwall and colluvium were bimodal, and those of the gully sediments and diluvium were single peak. ③ The mineral composition of the soils was mainly clay mineral Kaolinite, and followed by Quartz and Muscovite. The chemical components contained SiO2 and Al2O3, which were the top two in content. The content of Ti was the highest, and followed by S. [Conclusion] The physical properties of soil in different topographic position of the Benggangs displayed a certain differentiation phenomena from headwall to diluvium, and the hydraulic gravity composite erosion mechanism was the reason for the formation of this internal differentiation. Under strong chemical weathering, the composition of clay minerals was mainly composed of Kaolinite, and there was no obvious element migration and enrichment in the Benggangs.